Electronic Circuits Handbook for Design and Application - Tietze, Ulrich; Schenk, Christoph; Gamm, Eberhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book is written for students, practicing engineers and scientists. It covers all important aspects of analog and digital circuit design. Part I describes semiconductor devices and their behavior with respect to the models used in circuit simulation. Basic analog circuits are analyzed in four steps: large-signal transfer characteristic, small-signal response, noise and distortion. The treatment of digital circuits starts with the internal circuitry of logic gates and continues with combinatorial and sequential circuit design. Part II describes low frequency circuit design in various applications using operational amplifiers. The circuitry of A/D and D/A converters and their use in different signal sampling scenarios are considered. This part also presents the theory and design of analog and digital filters. Part III describes circuits for analog and digital communications over wireless channels. It includes comprehensive background information in terms of analog and digital modulations, radio frequency transmitters and receivers. The high-frequency behavior of passive components and the design of high-frequency filters, matching circuits, amplifiers and mixers are presented. The accompanying CD-ROM contains data sheets and simulation software. For analog circuit design the PSpice simulation suite, a tutorial and various examples are provided. This handbook and CD package offers a uniquely comprehensive and authoritative self-learning and reference resource.
Device Models and Basic Circuits -- Diode -- Bipolar Transistor -- Field Effect Transistor -- Amplifiers -- Operational Amplifiers -- Latching Circuits -- Logic Families -- Combinatorial Circuits -- Sequential Logic Systems -- Semiconductor Memories -- General Applications -- Operational Amplifier Applications -- Controlled Sources and Impedance Converters -- Active Filters -- Signal Generators -- Power Amplifiers -- Power Supplies -- Analog Switches and Sample-and-Hold Circuits -- Digital-Analog and Analog-Digital Converters -- Digital Filters -- Measurement Circuits -- Sensors and Measurement Systems -- Electronic Controllers -- Optoelectronic Components -- Communication Circuits -- Basics -- Transmitters and Receivers -- Passive Components -- High-Frequency Amplifiers -- Mixer.
Keywords: Engineering; Computer hardware; Physical measurements; Measurement; Control engineering; Robotics; Mechatronics; Microwaves; Optical engineering; Electronics; Microelectronics; Electronic circuits; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Measurement Science and Instrumentation; Microwaves, RF and Optical Engineering; Control, Robotics, Mechatronics; Computer Hardware; Electronic books